State of the art of QoE assessment methods, and emulation environments for the video service in LTE networks (2019)
This article presents a review of the methods currently used to measure Quality of Experience - QoE and Quality of Service - QoS for video service using techniques of streaming video through an internet service provider, the main differences are enunciated between objective and subjective metrics, use scenarios and disadvantages presented in a wireless environment. In addition, the radio access technology – RAN Long Term Evolution – LTE as the radio access technology and wireless technology most likely to be used in the coming years is presented, development tools for handling platforms emulation systems LTE are compared. Additionally, the article describes the challenges and research gaps in evaluating and measuring the quality of experience for video services supported by wireless technologies.